Efeitos do isolamento social nos aspectos motores e não motores em pessoas que vivem com doença de Parkinson no Amapá - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá)
With the emergence of the Corona Virus – COVID-19 and its potential risks to society, the orientation of social distancing has become, nowadays, one of the main measures for the prevention of this disease. In contrast to the benefits of this prevention measure, there is the hypothesis that physical distance may contribute to the emergence of motor and non-motor complications in these individuals. Objective: to investigate the impact of social isolation due to the COVID-19 pandemic on motor and non-motor aspects of daily life experiences of people living with Parkinson’s disease in Amapá. Materials and methods: This is a cross-sectional and analytical study with 27 individuals diagnosed with idiopathic PD in Amapá. Through a telephone survey, the motor and non-motor impacts of social distancing, because of COVID- 19, were analyzed. The variables studied were characterized using the mean and standard deviation, using the non-parametric Wilcoxon test. In the inferential analyses, a significance level of 5% was considered. Results: Most participants were male, corresponding to 77% of the total, with a mean age of 67.8 years (±10.02). The mean time of schooling was 10.1 years (±4.93), the diagnosis of PD was 69.6 months (± 77.07) and isolation, at the time of the interview, 7.3 weeks (± 1.82). The results demonstrate that the values of the variables of cognition, fatigue and gait and balance significantly decreased (p < 0.01) when compared before and after isolation. The mean value of cognition decreased from 1.11 (SD = 1.37) to -0.11 (SD = 0.70) (p = 0.002); the mean value of fatigue decreased from 0.59 (SD = 0.89) to -0.19 (SD = 0.40) (p = 0.005); the mean value for gait and balance decreased from 1.11 (SD = 1.19) to -0.30 (SD = 0.54) (p < 0.001). Conclusion: There was clinical worsening in the non-motor and motor aspects of cognition, fatigue, gait and balance due to the social distance caused by COVID-19. The negative impact of social distancing on individuals with PD residing in Amapá may have been aggravated by the reduction in the practice of physical activity and social participation. More studies aimed at this population are needed to elucidate the suggested relationships.
Keywords: Parkinson, Doença de; Isolamento social - COVID-19 (Doença); Distanciamento social - COVID-19 (Doença); CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL